Pengaruh Disiplin Kerja dan Etos Kerja Terhadap Produktivitas Karyawan PT. KS Bangunan Kota Tasikmalaya - Firdasari, Azizah Nur (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect simultaneously and partially on employee productivity which is influenced by work discipline and work ethic at PT. KS Tasikmalaya City Building. The method used in this research is a quantitative approach. The sample used amounted to 43 respondents. The data obtained are primary data through questionnaires. The analysis used is multiple linear regression analysis through SPSS Version 26. The results of this study indicate that work discipline and work ethic simultaneously have a significant effect on work productivity. Work Discipline partially has a significant effect on Work Productivity, Work Ethics partially has a significant effect on Work Productivity of employees of PT. KS Tasikmalaya City Building.